Ab initio quantum dynamical study of photoinduced ring opening in furan - Gromov, Evgeniy; Lévêque, C.; Gatti, F.; Burghardt, I.; Köppel, Horst (The journal of chemical physics, 2011)
The nonadiabatic photoinduced ring opening occurring in the two lowest excited singlet states of furan is investigated theoretically, using wave-packet propagation techniques. The underlying multidimensional potential energy surfaces (PESs) are obtained from ab initio computations, using the equation-of-motion coupled cluster method restricted to single and double excitations (EOM-CCSD), reported in earlier recent work [E. V. Gromov, A. B. Trofimov, F. Gatti, and H. Köppel, J. Chem. Phys. 133, 164309 (2010) https://doi.org/10.1063/1.3493451.]. Up to five nuclear degrees of freedom are considered in the quantum dynamical treatment. Four of them represent in-plane motion for which the electronic states in question (correlating with the valence 1B2(V) and Rydberg 1A2(3s) states at the C2v ground-state molecular configuration) have different symmetries, A′ and A′′, respectively. The fifth mode, representing out-of-plane bending of the oxygen atom against the carbon-atom plane, leads to an interaction of these states, as is crucial for the photoreaction. The nonadiabatic coupling and conical intersection cause an electronic population transfer on the order of ∼10 fs. Its main features, and that of the wave-packet motion, are interpreted in terms of properties of the PES. The lifetime due to the ring-opening process has been estimated to be around 2 ps. The dependence of this estimate on the nuclear degrees of freedom retained in the computations is discussed.